2014
DOI: 10.1136/gutjnl-2014-308163
|View full text |Cite
|
Sign up to set email alerts
|

Association between antiviral treatment and extrahepatic outcomes in patients with hepatitis C virus infection

Abstract: Antiviral treatment for HCV is associated with improved renal and circulatory outcomes, but unrelated to catastrophic autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
196
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(219 citation statements)
references
References 44 publications
17
196
1
5
Order By: Relevance
“…SVR in patients without cirrhosis or extrahepatic advanced disease is generally associated with the resolution of liver disease and can reduce the HCV-related extra-hepatic disease burden, i.e. diabetes, kidney impairment, lymphoproliferative disorders (LPD) and cardiovascular complications, ultimately leading to an increased survival (2,3,(7)(8)(9)(10)(11)(12)(13)(14)(15). Cirrhotic patients who achieve SVR may have liver fibrosis regression, A c c e p t e d M a n u s c r i p t 6 and reduced risk of hepatic decompensation and portal hypertension complications although they maintain a residual risk of HCC (16)(17)(18)(19)(20).…”
Section: Whom To Treat?mentioning
confidence: 99%
“…SVR in patients without cirrhosis or extrahepatic advanced disease is generally associated with the resolution of liver disease and can reduce the HCV-related extra-hepatic disease burden, i.e. diabetes, kidney impairment, lymphoproliferative disorders (LPD) and cardiovascular complications, ultimately leading to an increased survival (2,3,(7)(8)(9)(10)(11)(12)(13)(14)(15). Cirrhotic patients who achieve SVR may have liver fibrosis regression, A c c e p t e d M a n u s c r i p t 6 and reduced risk of hepatic decompensation and portal hypertension complications although they maintain a residual risk of HCC (16)(17)(18)(19)(20).…”
Section: Whom To Treat?mentioning
confidence: 99%
“…In a unique and large natural history study, Lee et al showed that patients with chronic HCV infection had a cumulative non-liver-related mortality rate of 19.8% after 18 years of follow-up, which was considerably higher as compared to those patients who cleared their HCV infection (11.0%) and those who never encountered HCV (12.2%) (2). Although not as extensively as for the cirrhosis-related complications, data are slowly emerging that achievement of SVR is also associated with a reduced occurrence of solid extra-hepatic clinical endpoints such as renal failure and cardiovascular events (3,4). These potential clinical benefits may explain the reduced occurrence of death due to extrahepatic causes in case of SVR, which Tada et al describe here.…”
Section: See Article On Page 817mentioning
confidence: 68%
“…Rates of acute coronary syndrome and ischemic stroke were significantly reduced in patients treated with peginterferon and ribavirin compared to untreated patients [39]. Although this association was found in studies originating from Far East countries, Western European and American studies, as well as a recent metaanalysis, have not established a clear correlation of HCV infection and increased cardiovascular and cerebrovascular risk [40,41]. Likewise, the pathogenetic mechanism through which HCV leads to accelerated atherosclerosis has not been fully elucidated.…”
Section: Cardiovascular Diseasementioning
confidence: 89%